(untitled) (American Journal of Islam and Society, 2011)
Mullā Ṣadrā and Metaphysics: Modulation of Being appears at a time when the study of Ṣadr al-Dīn al-Shīrāzī’s philosophy has reached a critical mass. Critical editions of Shirazi’s works are available, and there are numerous studies on aspects of his thought. Rizvi has done an excellent job of synthesizing this information, examining it critically and building on it to push Sadrian studies forward. The philosophical question that Rizvi explores in this book is: “[h]ow can we reconcile the vision of the unity in existence and the quest for a singular explanation for reality with our everyday, phenomenal experience of plurality and multiplicity?” (xi). Rizvi approaches this question both as a philosopher and a historian of philosophy. The aim of this study is to examine Shirazi’s central philosophical idea—the modulation of being—and to use this idea to understand his philosophy. Whereas most studies on Shirazi have focused on Kitāb al- Mashā‘ir or al-Ḥikma al-‘arshīya, Rizvi focuses on the section on metaphysics in Shirazi’s most important work Al-Ḥikma al-muta‘ālīya, or simply the Asfār. There are two major theses in this book. One, “tashkīk is a hermeneutic concept which describes the threefold division of being and its gradation,” and two, “gradation and modulation occur in each mode of being” (3). As Rizvi points out, “being in expression” is the foundation of Shirazi’s semantic theory; “mental being” is about epistemology and psychology; and “actual being” covers metaphysics. “Modulation,” then, is the axis around which different branches of Shirazi’s philosophy revolve ...